ANALISIS PENENTUAN TARIF SEWA KAMAR DENGAN METODE TITIK IMPAS (BEP) PADA BIGLAND SENTUL HOTEL DAN CONVENTION - Muhammad Irfan Septiani; Indra Cahya Kusuma; Didi, Didi (Jurnal Cakrawala Ilmiah, 2024)
With the large number of four-star hotel room occupancy in Bogor, hoteliers must be wise in setting room rates in competition for the continuity of the hotel business, along with the effectiveness of room rates affecting the level of hotel room sales. This study aims to determine the breakeven point of several types of rooms for the policy of setting room rental rates at hotel occupancy rates during low season at Bigland Sentul Hotel & Convention. The analytical method used is descriptive where this method is used to describe and analyze the results of the research then conclusions are drawn and the type of research used is descriptive qualitative. Data collection techniques using interviews, observation, and documentation. Based on the results of the research conducted, it shows that the determination of management rates is higher than the rates for activity-based costing.